An assessment into the challenges faced by students in the use of information communication technology (ICT) at primary level - Jori, Merjury (Midlands State University, 2017)
The study assessed the challenges faced by students in using Information Communication Technology (ICT) at primary level. The research was carried out in Cluster five of Glenview Mufakose District in Harare. In order to get an insight on the challenges, different authorities were reviewed. The descriptive survey design was adopted in this study. Probability and non-probability sampling techniques were employed in order to select participants in this research. Five teachers, twenty pupils, 5 heads and ten parents were used as participants. Data was collected through the use of questionnaires, interviews and observations administered in five schools. The findings of this survey showed that, a wide range of ICT challenges hinder its efficient implementation. These include; gender inequalities in relation to how ITC tools are used in schools and at family level, shortage of ICT equipment, infrastructure, lack of trained teachers and inadequate time to teach practical lessons. However, possible solutions to these problems include; holding awareness campaigns in schools so that teachers and parents are educated on how they empower the girl child so that they have confidence in using ICT gadgets. Schools must acquire ICT equipment, build computer laboratories and more ICT teachers should be trained to teach ICT at primary level. It was recommended that teachers must do away with gender stereotypes in the field of ICT. The government must prioritize the acquisition of ICT equipment for schools and training of teachers in ICT.